Derivation of a climate change adaptation index and assessing determinants and barriers to adaptation among farming households in Nepal. Issue 101 (November 2019) - Khanal, Uttam; Wilson, Clevo
Highlights: An integrated climate change adaptation index developed taking into account the importance of adaptation measures and the scale of adoption. Access to credit and extension services, climate information, and adaptation beliefs are important factors influencing adaptation. Farming households' social, economic and attitudinal characteristics should be considered while planning and implementing agricultural adaptations. Abstract: This paper attempts to fulfill the methodological gap in measuring adoption of climate change adaptation practices among smallholder farmers in less developed countries. It explains the derivation of an adaptation index taking into account the importance of adaptation practice and the scale of adoption. Based on information collected through a questionnaire survey of 720 farming households in six districts of Nepal, this study further identifies the factors influencing the farmers adoption of climate change adaptation practices. The multiple regression models revealed 11 variables significantly influencing the adoption of climate change adaptation practices. The variables found significant are age and education of the household head, family size, income sources, access to credit and extension services, number of plots under cultivation, past climate change experience, access to climate information, acceptance of climate change, and belief on adaptation. This indicates that policies aimed at planning and implementation of adaptation programs should emphasize the crucial role of social, economic and attitudinal characteristics of farming households.